Growth of Various Chrysanthemum (Chrysanthemum morifolium R.) Cultivars Cuttings on Different Auxin Type - Agus Rahman; Setyono Setyono; Budi Winarto (JURNAL AGRONIDA, 2018)
This study aims to obtain qualified seedlings, and speed up the rooting of some varieties ofchrysanthemum (Chrysanthemum morifolium R.) cuttings use synthetic and naturally plant growthregulator (auxin). Research results are expected to be an alternative method of application effectiveand environmentally friendly plant growth regulator. The research was conducted from March toApril 2013 at the Research Institute of Ornamental Plants (Balai Penelitian Tanaman Hias). Theexperimental design used is completely randomized design (CRD) factorial. The first factor is thetype of auxin which consists of four levels ie control, indole acetic acid (IAA), naphthalene aceticacid (NAA), pregnant cow urine, and not pregnant cow urine. The second factor is the type ofchrysanthemum varieties which consists of four levels ie spray type of Puspita Pelangi, spray typeof Puspita Nusantara, standard type of Sakuntala, and standard type of Pasopati. The resultsshowed that type of chrysanthemum cultivars and type of auxin not affected the percentage of livecuttings, percentage of rooted cuttings and percentage of sprouted cuttings. The cuttings root ofplant that given by pregnant cow urine is better than other treatments. Cuttings root length, andnumber of primary root of Pasopati is better than other cultivars. The interaction influence betweenthe type of auxin and chrysanthemum cultivars found only in the number of secondary roots,diameter of root and length of the shoot cuttings at 12 DAP.Keywords: Chrysanthemum morifolium R., cow urine, NAA, spray type